THE EFFECTS OF TEXTUAL ENHANCEMENT AND STRUCTURED INPUT ACTIVITIES ON THE ACQUISITION OF THE ITALIAN NOUN-ADJECTIVE AGREEMENT (Italiano LinguaDue, 2015)
La concordanza tra genere e aggettivo è una caratteristica morfologica presente nella lingua italiana che è di difficile acquisizione da parte degli studenti che hanno familiarità solo con lingue in cui la concordanza è del tutto assente. Il presente articolo presenta uno studio condotto presso l’Università degli Studi di Milano che si propone di comparare l’efficacia di due diversi modelli di didattica nell’acquisizione della capacità di utilizzare correttamente la concordanza di genere tra nome e aggettivo da parte di discenti di L2 di madrelingua cinese. I due metodi utilizzati nella sperimentazione sono il Textual Enhancement (Sharwood Smith, 1991)e le Structured Input Activities (Van Patten 1996,2004). La sperimentazione, strutturata in tre fasi (Benati, 2004), è stata condotta presso il Centro Marco Polo su un gruppo di sinofoni, studenti di italiano L2 di livello A2-B1. I risultati hanno confermato che sia il Textual Enhancement che le Structured Input Activities sono metodi d’insegnamento validi che aiutano i discenti ad elaborare particolari strutture morfologiche come la concordanza di genere. Tuttavia è emerso che il gruppo sottoposto al test con trattamento Structured Input Activities ha ottenuto risultati migliori rispetto al gruppo sottoposto a Textual Enhancement  The present study seeks to explore the effects that different types of instructions, namely Textual Enhancement and Structured Input Activities, can have on the acquisition of noun-adjective gender agreement by L2 Italian learners. A view of the theoretical backgrounds together with a review of the studies conducted on textual enhancement and structure input activities provide an overview of the main topics of the research. The present research aims to investigate whether textual enhancement and structured input activities help learners to make significant grammatical gains when exposed to these types of instruction and also which one facilitate better improvements. To do so, an experimental research has been conducted at the Università degli Studi di Milano in Milan, Italy. A group of Chinese student learning Italian has been pre-tested, then divided in two groups and exposed to different types of instructions, namely textual enhancement and structured input activities and finally tested in order to see the effects of the exposure to different types of instructions. Results showed that textual enhancement and structured input activities are positive instructions that help learners to notice the target form and comprehend it. Furthermore the results showed that the group who undertook the SIA tests showed a significantly larger improvement than the group who undertook the TE tests.